Inside Back Cover: Retina‐Inspired Organic Photonic Synapses for Selective Detection of SWIR Light (Angew. Chem. Int. Ed. 6/2023). Issue 6 (12th January 2023) - Wang, Song; Chen, Hao; Liu, Tianhua; Wei, Yanan; Yao, Guo; Lin, Qijie; Han, Xiao; Zhang, Chunfeng; Huang, Hui
Abstract : A retina‐inspired photonic synaptic device based on a novel conjugated polymer and fullerene derivatives with selective response to SWIR light is reported by Hui Huang et al. in their Research Article (e202213733) . The devices demonstrate superior synaptic characteristics with noise reduction functions, thus paving the way for the development of organic electronics.